2017
DOI: 10.1080/20477724.2017.1340128
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem resistant Klebsiella pneumoniae isolated from bloodstream infection: Indian experience

Abstract: Increased incidence of multidrug resistant (MDR) Gram negative infection has resulted in high rates of morbidity and mortality. Klebsiella pneumoniae is one of the commonest MDR pathogens causing bacteraemia with limited therapeutic options such as colistin and tigecycline. Present study focused on molecular characterisation of MDR K. pneumoniae from bloodstream infection and their clinical outcome. A total of 115 K. pneumoniae from January 2015 to September 2016 were included in the study which comprised of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 34 publications
7
54
3
1
Order By: Relevance
“…As expected, most cases of carbapenemresistant bacteraemia (87%) in this study were healthcare-acquired. This is consistent with the results of several studies from different parts of the world, which have attributed most of the carbapenemresistant blood isolates to healthcare (Chen et al, 2018;Hattemer et al, 2013;Veeraraghavan et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…As expected, most cases of carbapenemresistant bacteraemia (87%) in this study were healthcare-acquired. This is consistent with the results of several studies from different parts of the world, which have attributed most of the carbapenemresistant blood isolates to healthcare (Chen et al, 2018;Hattemer et al, 2013;Veeraraghavan et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…An Indian study reported 5% community-acquired K. pneumoniae bloodstream infection as carbapenem-resistant (Veeraraghavan et al) [9]. Our case of community-acquired pneumonia, along with bacteremia, also showed carbapenem resistance, which signifies the increasing carbapenem resistance in the community.…”
Section: Casesupporting
confidence: 55%
“…The organism can have more than one type of carbapenemase-producing gene. Indian study reported CRKp from blood isolates (n = 115) producing blaNDM in 19% and blaOXA48-like in 13% and a combination of both in 28% (Veeraraghavan et al) [9]. A similar study of 30 isolates of Carbapenem-resistant Acinetobacter baumannii reported that all 30 isolates (100%) were positive for blaOXA-51 like gene, blaIMP-1, and blaVIM-1 genes (Niranjan et al) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The bla NDM positive isolates belonging to ST410 and ST405 harboured only the bla NDM-5 variant, whereas ST167 and ST131 isolates had bla NDM-4 and bla NDM-1 respectively, in addition to bla NDM-5 . Interestingly only two isolates out of 60 MDR E. coli had bla NDM-1 , while it is still common among other species of MDR clinical pathogens in India [18]. From Hong Kong, a previous report identified bla NDM-1 as common among E. coli though the sample size was lesser [19], whereas in central China, bla NDM-1 and bla NDM-5 occurrence in E. coli has been reported in equal numbers [20].…”
Section: Discussionmentioning
confidence: 91%